Erozija družinske politike - Dragoš, Srečo (Socialno delo, 2017)
The paper analyzes the proposal for the Resolution on Family Policy 2018-2028, which was put into the public debate by the ministry for the relevant area. This document raises mixed feelings. On the one hand, its content is expected, as it is a consistent reflection of developments in the field of social policy. On the other hand, it is a surprise as it offers some radical solutions that we were not familiar with so far. For this resolution, family policy is definitely (declaratively) separated from social policy and transformed into a natality policy. The paper deals with the harmfulness of such policy in four sections, which show "blind spots" of the planned policy already by their names: autonomy, birth rate, inequality and binding container. At the end of the paper, a suggestion is given as to how to resolve the new family policy without making it dysfunctional. But the proposed solution is pessimistic, because in current political framework it is not realistic. But there are no others.
Keywords: družina; family; socialna politika; socialna država; welfare state; autonomy; avtonomija; social work; socialno delo; nataliteta